2011
DOI: 10.1007/s13277-011-0253-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of DNA repair genes (XRCC1, XPD, and OGG1) in squamous cell carcinoma of head and neck in North India

Abstract: Squamous cell carcinoma of head and neck (SCCHN) is the sixth most common cancer globally, and in India, it accounts for 30% of all cancer cases. Epidemiological studies have shown a positive association between defective DNA repair capacity and SCCHN. The underlying mechanism of their involvement is not well understood. In the present study, we have analyzed the relationship between SCCHN and the expression of DNA repair genes namely X-ray repair cross-complementing group 1 (XRCC1), xeroderma pigmentosum grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…The rs25487 located in the region of the BRCT1 binding domain, and mutations in the BRCT1 domain of BRCA1 have been implicated in the altered function of this tumor suppressor gene (Sterpone et al, 2010). Previous several studies have shown that XRCC1 399 variant allele was associated with increased gene expression of various cancers, such as head and neck cancer, ovarian cancer and hepatocellular carcinoma (Cheng et al, 2012;Kumar et al, 2012;Yuan et al, 2012). The results of our study are in line with previous studies, suggesting a strong increased risk of glioma among individuals carrying with XRCC1 399G/G or XRCC1 194T/T genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The rs25487 located in the region of the BRCT1 binding domain, and mutations in the BRCT1 domain of BRCA1 have been implicated in the altered function of this tumor suppressor gene (Sterpone et al, 2010). Previous several studies have shown that XRCC1 399 variant allele was associated with increased gene expression of various cancers, such as head and neck cancer, ovarian cancer and hepatocellular carcinoma (Cheng et al, 2012;Kumar et al, 2012;Yuan et al, 2012). The results of our study are in line with previous studies, suggesting a strong increased risk of glioma among individuals carrying with XRCC1 399G/G or XRCC1 194T/T genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the combined effect of a panel of DNA repair genes that interact in different DNA repair pathways may amplify the effects of individual variation in expression level and enhance predictive power. Although reduced expression of DNA repair genes has been shown to be associated with squamous cell carcinoma of head and neck (Kumar et al, 2012) and smoking-related cancers such as lung cancer (Wei et al, 1996); few studies have evaluated the expression level of DNA repair genes in the etiology of cervical cancer. Hence, we measured the relative expression levels of NER genes (ERCC1, ERCC2, and ERCC4) and BER gene (XRCC1) in SiHa cells on treatment with Noni alone, Cisplatin alone, and combination of both Noni and Cisplatin for 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent clinical evidence suggests that ERCC1 levels predict response to platinum-based therapies in nonsmall cells lung cancer (Olaussen et al, 2007) and bladder cancer (Bellmunt et al, 2007). Reduced expression of ERCC2 has been reported in squamous cell carcinoma of head and neck (Kumar et al, 2012). Chinese hamster cell lines defective in ERCC4 were found to be hypersensitive not only to UV but also to DNA interstrand cross-linking agents .…”
Section: Dna Repair Genes (Ner and Ber)mentioning
confidence: 92%
See 2 more Smart Citations